Efficacy and safety of deflazacort in children with an initial episode of idiopathic nephrotic syndrome - a randomized controlled trial - Islam, Mohammad R.; Mia, Abdul A.; Ahmed, Tahfim; Jahan, Nusrat; Kabir, Rashadul; Baki, Mohammad A.; Al-Aziz, S. M. Ahsanul K. (International Journal of Contemporary Pediatrics, 2025)
Background: Idiopathic nephrotic syndrome (INS) is the most common glomerular disease in children. Prednisolone has been the standard first-line therapy, but deflazacort, a synthetic corticosteroid, has shown promise with potentially fewer side effects. This study aimed to compare the efficacy and safety of deflazacort versus prednisolone in children with an initial episode of INS. Methods: This randomized controlled trial was conducted in the Department of Pediatric Nephrology, National Institute of Kidney Diseases and Urology (NIKDU), Dhaka, Bangladesh, from June 2019 to January 2021. In this study, we included 83 children, aged 2 to 12 years, who had Idiopathic nephrotic syndrome and visited the outdoor department and were admitted to the pediatric nephrology department of NIKDU. Patients were divided into two treatment groups – group A patients were prescribed prednisolone, and group B patients were prescribed deflazacort. Results: The mean age was significantly higher in the deflazacort group (4.97±2.11 years) compared to the prednisolone group (3.87±1.23 years), with a statistically significant p value of 0.007. The mean time to induce remission was significantly shorter in the deflazacort group (7.87±3.33 days) compared to the prednisolone group (9.82±3.43 days; p=0.02). Although relapse rates were higher in the prednisolone group at 3 and 6 months, the differences were not statistically significant. Complications like moon face and buffalo hump occurred more frequently in the prednisolone group, but without statistical significance. No significant differences were observed in growth parameters, blood pressure, cholesterol, or random blood sugar (RBS) levels between the two groups during follow-up. Conclusions: This study showed that deflazacort induced remission in a shorter time compared to prednisolone in children with an initial episode of INS. While both treatments were similarly effective in achieving remission, the deflazacort group experienced fewer relapses and a lower incidence of side effects during the follow-up period.